Perancangan Media Informasi Berbasis Video Dokumenter Pengenalan Produk Bio Gas Kelompok Tani Simantri Sandakan, Sulangai, Petang - Putra, I Putu Satria Udyana; Asana, I Made Dwi Putra; Santika, Putu Praba; Atmaja, Ketut Jaya; Putu Wirayudi Aditama; Suandana, Ni Putu Widantari; I Wayan Krishna Sangging Wiguna (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The province of Bali, Indonesia, as a tropical destination with abundant natural resources, exhibits a serious focus on the agriculture and livestock sectors. The Simantri program, as a local government innovation, aims to accelerate the adoption of agricultural technology in rural communities. Bio gas, as a renewable energy alternative, emerges as a crucial solution amid the challenges posed by unsustainable fossil fuels. The Simantri Farmers Group in Br. Sandakan, Sulangai Village, faces challenges in introducing their bio gas products to the community. In the Community Service activity, a documentary video was created as an effective informational medium, successfully introducing, enhancing understanding, and raising awareness about the use of bio gas among the community. The video not only promoted the product but also strengthened the role of Simantri in village development and tourism potential. The success of this activity reaffirms that utilizing video-based informational media is an effective step in introducing innovations, enhancing understanding, and supporting the well-being of the local community.